Alcohol consumption among high-risk Thai youth after raising the legal drinking age - Susan G. Sherman (2018)
Objective: Methamphetamine and alcohol are the leading substances abused by Thai youth. In 2008 the government passed laws that limited alcohol availability and increased the legal drinking age from 18 to 20. We assessed whether the law reduced drinking among methamphetamine-using 18-19 year olds in Chiang Mai. Method: The study compares drinking patterns among methamphetamine smokers aged 18-19 years (n= 136) collected prior to the legal changes, to a comparable post-law sample (n= 142). Statistical tests for differences between the pre- and post-law samples on problem drinking and recent drinking frequency and drunkenness were conducted. Logistic regression modeled the relative odds of frequent drunkenness, controlling for demographic characteristics. Results: A high prevalence of problematic drinking was present in both samples, with no difference detected. The post-law sample reported a significantly higher median days drunk/month (9 vs. 4, p≤ 0.01); in adjusted analysis, frequent drunkenness ( > 5.5 days/month) was more common in the post-law compared to pre-law period in the presence of other variables (AOR: 2.2; 95%CI: 1.3, 3.9). Post-law participants demonstrated a low level of knowledge about the law's components. Conclusions: The study suggests that the new laws did not reduce drinking among high-risk, methamphetamine-smoking 18-19 year olds; rather, the post-law period was associated with increased drinking levels. The data indicate that the law is not reaching high-risk under-aged youth who are at risk of a number of deleterious outcomes as a result of their substance use. © 2013.